Chemical fingerprinting and quantitative analysis of a Panax notoginseng preparation using HPLC-UV and HPLC-MS - Shao Qing; Shi Peiying; Yao Hong; Fan Xiaohui (BMC, 2011)
Abstract Background Xuesaitong (XST) injection, consisting of total saponins from Panax notoginseng, was widely used for the treatment of cardio- and cerebro-vascular diseases in China. This study develops a simple and global quality evaluation method for the quality control of XST. Methods High performance liquid chromatography-ultraviolet detection (HPLC-UV) was used to identify and quantify the chromatographic fingerprints of the XST injection. Characteristic common peaks were identified using HPLC with photo diode array detection/electrospray ionization tandem mass spectrometry (HPLC-PDA/ESI-MSn). Results Representative fingerprints from ten batches of samples showed 27 'common saponins' all of which were identified and quantified using ten reference saponins. Conclusion Chemical fingerprinting and quantitative analysis identified most of the common saponins for the quality control of P. notoginseng products such as the XST injection.